Prevención de diabetes mellitus tipo II en diabetes gestacional. Hospital Provincial General Docente. Riobamba, 2021 - Andrade Andrade, Azaria Mishelle (2022)
ABSTRACT: The American Diabetes Association (ADA) defines Gestational Diabetes Mellitus (GDM) as diagnosed in the second or third trimester of pregnancy without a history of diabetes. One of the maternal consequences of gestational diabetes is the development of type 2 diabetes mellitus (DM2), a growing public health problem associated with severe health complications, thus reducing the quality and life expectancy of mothers. Evidence suggests that lifestyle interventions aimed at people at high risk of DM2 can prevent or delay its manifestation. Therefore, a diagnosis of gestational diabetes represents a window of opportunity for preventive intervention. Objective: To identify the risk factors most associated with the development of gestational diabetes and that contribute to triggering type 2 diabetes mellitus in women treated at the Hospital Provincial General Docente de Riobamba in the period January-December 2021. Method and materials: A retrospective study was carried out, examining 177 medical records (CH) of women diagnosed with gestational diabetes, allowing: them to identify the factors most associated with the risk of developing gestational diabetes and that contribute to triggering type 2 diabetes mellitus. Results: Of the 177 (CH), 47 developed type 2 diabetes mellitus. Most of the patients, represented by 41.81%, were over 35 years old. Conclusion: the risk factors most associated with the development of gestational diabetes and that contribute to triggering type 2 diabetes mellitus were: advanced age (>35 years), history of DM2 in first-degree relatives, diagnosis of GDM while they were in the second trimester of pregnancy, history of GDM, overweight before pregnancy, and weight gain during pregnancy